Life Chances in Turkey : Expanding Opportunities for the Next Generation - Hentschel, Jesko; Aran, Meltem; Can, Raif; Ferreira, Francisco H.G.; Gignoux, Jeremie; Uraz, Arzu (World Bank, 2012)
Life chances explore the state of equality of opportunities in Turkey. It builds on the concepts and ideas presented in the World Development Report 2006: equity and development. The authors assess how today's distribution of wealth and the success of children in learning to read and write are shaped by the past, by factors predetermined at birth, factors over which today's children and families have no control: one's gender, parents' and grandparents' education, region and area of birth, or mother tongue. Some of the findings are stark, especially as they pertain to how the opportunities today's children have affect the future of the country: a girl born in a remote village to a poor family and parents with primary education degrees will very likely struggle in almost every area of her development. Compared with a boy born to well-off, highly educated parents in one of the urban centers in the country's west, that girl is four times as likely to suffer from low birth weight, one-third as likely to be immunized, and ten times as likely to have her growth stunted as a result of malnutrition. Similarly she has a one-in-five chance of completing high school, whereas the boy will likely finish school and move on to college. Life chances shows how investing in early childhood education has huge payoffs, for disadvantaged children as well as social and economic development at large. This book goes beyond tradeoffs between efficiency and equity. It shows that a focus on equity, equality of opportunities, can also lead to enhanced efficiency, once the productive capabilities of all citizens are nurtured to their fullest extent regardless of the luck of the draw at birth.